Kosmologi Perkawinan Dalam Pandangan Suku Osing : Studi Di Desa Kemiren Banyuwangi - Maryuliyanto Maryuliyanto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Kemiren Village Banyuwangi is a traditional Osing village because it still adheres to its customs. One of the things that regulates customary law is marriage. Marriage according to customary law is one of the most important events in people's lives. Because according to indigenous peoples, marriage does not only involve a man and a woman as potential brides, but also binds the two families together. The success of a household in realizing a happy life, especially in indigenous peoples, is largely determined by the intervention of relatives and family, which starts when they are about to get married or when there is a conflict in the household. In this case, it is very dependent on the rituals that were usually performed beforehand and asked for the opinion of the traditional leader. The research focuses on this namely the cosmology of marriage in the view of the Osing tribe of Banyuwangi. This research was conducted with the objectives to analyze the cosmology of marriage in the perspective of the Banyuwangi Osing tribe, The research method used in this research is empirical research using descriptive qualitative, meaning that this research seeks to describe, record, analyze and interpret what is being studied, through observation, interviews and studying documentation. The research approach used in this study is the sociological approach. The sociological approach is an approach used to describe the state of society complete with structures, layers and various other interrelated social phenomena. Based on the results of the research that has been done, the researcher concludes that; First, marriage is a sacred bond to unite two people who have a relationship or a sense of love as a gift to be grateful for. Kemiren Banyuwangi Village is a district that has a diverse community and has a different culture for each region and tribe, one of which is the tradition of marriage. Second, family. Second, in living a household life, of course there are times when there are disputes between husband and wife. In the customary community of the Osing Tribe when there is a conflict or even a divorce, they resolve it according to customary law, because in each customary law there is a pattern of settlement when a problem occurs.